An objective approach to model reduction: Application to the Sirius wheat model☆ - Crout, N.M.J. (Elsevier Science Publishers B.V, 2014)
•We demonstrate the application of systematic model reduction to a complex crop model.•The model was manipulated under software control replacing variables with constants.•Redundancy in representation of nitrogen physiology and temperature was found.•The level of detail in Sirius is defensible if detailed prediction is required.•The approach increases the efficiency and rigour of model evaluation.